Comprehensive Evaluation of Manufacturing Sector Performance in the COVID-19 Pandemic Era (2019-2021) : A Systematic Literature Review - Zukhruf, Kamiliya; Fresilia, Alya (Draf Solusi Indonesia, 2025)
Companies' bottom lines took a major hit during the COVID-19 epidemic, especially those in the industrial industry. This research compares the financial performance of IDX-listed manufacturing businesses before and after the pandemic using many metrics, including ROA, ROE, NPM, Current Ratio, and TATO. We used a quantitative approach using a Wilcoxon Signed Rank Test and a Paired Sample tTest to analyse financial data from 2018 – 2021. The results indicate significant changes in profitability and efficiency ratios. Additionally, the study emphasizes the relevance of non-financial factors such as digital transformation and government policies, which remain underexplored in Indonesia. These findings align with prior research and provide insights for companies to formulate stronger strategies in facing economic crises, especially in the post-pandemic recovery phase.